2016
DOI: 10.3847/0004-6256/152/6/159
|View full text |Cite
|
Sign up to set email alerts
|

THE 3–4 μm SPECTRA OF JUPITER TROJAN ASTEROIDS

Abstract: To date, reflectance spectra of Jupiter Trojan asteroids have revealed no distinctive absorption features. For this reason, the surface composition of these objects remains a subject of speculation. Spectra have revealed, however, that the Jupiter Trojan asteroids consist of two distinct sub-populations that differ in the optical to near-infrared colors. The origins and compositional differences between the two sub-populations remain unclear. Here, we report the results from a 2.2-3.8 μm spectral survey of a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…Fastforwarding to more recent work, a study of KLband spectra revealed the first incontrovertible absorption feature centered around 3.1 µm on several Trojans (Brown 2016). This feature has typically been associated with fine surface water frost, but is also consistent with an N-H stretch feature attributable to ammoniated clays.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Fastforwarding to more recent work, a study of KLband spectra revealed the first incontrovertible absorption feature centered around 3.1 µm on several Trojans (Brown 2016). This feature has typically been associated with fine surface water frost, but is also consistent with an N-H stretch feature attributable to ammoniated clays.…”
Section: Introductionmentioning
confidence: 63%
“…Irradiation experiments on polystyrene-coated olivine showed the opposite trend, with an initial steep UV and flat visible spectral shape changing to a more linear spectrum with increasing irradiation dosage (Kaňuchova et al 2010). While previous spectral modeling of Trojans has typically limited the mass fraction of complex organics due to the absence of associated major absorption features in the near-infrared (e.g., Jewitt & Luu 2000;Emery & Brown 2003;Dotto et al 2006;Fornasier et al 2007;Emery et al 2011), the KL-band spectra of LR Trojans show minor absorptions at 3.3 and 3.4 µm that are consistent with aromatic and aliphatic hydrocarbons, respectively (Brown 2016).…”
Section: Comparison With Other Published Uv Spectramentioning
confidence: 90%
“…It is presumed that other Ceres‐type objects share the surface composition of Ceres (or a similar composition) in the absence of other information to the contrary. The composition of the Themis types is interpreted to include water ice frost and organics (Campins et al, ; Rivkin & Emery, ), though the expected short lifetime for ice on asteroidal surfaces has led to alternate proposed compositions such as goethite (Beck et al, ) or ammoniated minerals (Brown, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Detection of diagnostic spectral absorption features in these groups of Trojans would allow for a detailed mineralogical characterization of their surfaces. The absence of observed features in the 3-µm region by Emery and Brown (2004) Brown (2016) detected spectral curvature between 3.0-3.5 µm in several large lessred Trojans (including Patroclus), which may indicate the presence of ices or organic species and would strengthen the connection between Trojans and a volatile-rich origin. Atmospheric extinction in this wavelength region can limit the definition of the spectral continuum, which is necessary to tie these low signal-to-noise features to a specific hypothesis.…”
Section: Introduction (Trojan Surfaces)mentioning
confidence: 93%